SISTEM INFORMASI PENGELOLAAN DATA LAPORAN HASIL PRODUKSI BERBASIS WEBSITE PADA PT. NIKONA GRAHA TANGERANG - Giandari Maulani; Kartika Chandra Buana Sejati; Zahrotul Hayati (UNIVERSITAS RAHARJA, 2016)
Development of technology and information in the age of globalization is currently growing very rapidly. Apart from being a medium of communication and information, the information technology and also help people in completing all the work. Computers have utility in detecting errors in the data though and can do the job beyond human ability to delay a job can be avoided. One of them at Graha PT.Nikona Tangerang often face problems in data management reporting production results. In the data management reports on the production done by the production still has some shortcomings, namely the process of recording reports of production carried out by the production department still use paper and can not do inputting reports production results on the same day as reports production results recorded in the form of production using paper so it takes a long time in processing the data and storing the data is still less secure and less well because of the lack of a good data storage such as paper reports production results in piles on the table so that the report output could be lost and can be mixed to report the results of which are already in production inputs. Based on the above problems, the authors propose to make application data management reports production results are easy to operate quickly, making applications easily accessed by the production department and has a secure data storage so that data that is not easily lost and data storage into more integrated.